1996
DOI: 10.1046/j.1365-2567.1996.d01-680.x
|View full text |Cite
|
Sign up to set email alerts
|

Afferent lymph veiled cells stimulate proliferative responses in allogeneic CD4+ and CD8+ T cells but not γδ TCR+ T cells

Abstract: SUMMARYDendritic cells were identified in afferent lymph derived by lymphatic cannulation of cattle, stained with monoclonal antibody (mAb) to the bovine workshop cluster 6 (WC6) antigen, which is highly expressed on bovine afferent lymph veiled cells, and sorted with a fluorescence-activated cell sorter. These cells expressed major histocompatibility complex (MHC) class I and II and CD1b but not CD14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…On the other hand, also cellular analysis, represented almost exclusively by mononuclear cells, supports the hypothesis that seroma fluid is an accumulation of afferent lymph. Further supporting this hypothesis, the presence of large mononuclear cells only partially expressing CD14 is reminiscent of "veiled cells" detectable in afferent lymph [18]. Also, the finding of extremely high levels of IL-6 in seroma is strongly suggestive for an accumulation of afferent lymph.…”
Section: Discussionmentioning
confidence: 68%
“…On the other hand, also cellular analysis, represented almost exclusively by mononuclear cells, supports the hypothesis that seroma fluid is an accumulation of afferent lymph. Further supporting this hypothesis, the presence of large mononuclear cells only partially expressing CD14 is reminiscent of "veiled cells" detectable in afferent lymph [18]. Also, the finding of extremely high levels of IL-6 in seroma is strongly suggestive for an accumulation of afferent lymph.…”
Section: Discussionmentioning
confidence: 68%
“…The gd T cells may also be involved in Ag presentation independently from dendritic cells. In work performed by Howard et al (40) + cells were eliminated, the breadth of immune responses to virus often compensates for lacking a particular function. The Juleff study did not include multiple Ab treatments to address what happens when multiple responding cell populations are blocked/eliminated in the same animal, most likely due to the very high cost of such a study.…”
Section: Discussionmentioning
confidence: 99%
“…In the bovine system it has been reported that purified WC1 ϩ T cells require the addition of exogenous IL-2 for proliferation in response to Thileria annulata-infected autologous cells but that IL-2 alone induces a limited WC1 ϩ proliferative response (16). Other studies have also reported that IL-2 alone induces minimal proliferation of bovine WC1 ϩ cells, implying that IL-2 is required as a secondary signal for activation of ␥␦ cells (15,29), driving them to proliferation (16). In the present study, the high degree of proliferation of purified WC1 ϩ T cells in response to MBSE and CF was observed only in infected animals, indicating the specificity of the response to M. bovis antigens, with a possible requirement for IL-2 and/or other cytokines supplied by other cells.…”
Section: Discussionmentioning
confidence: 99%